“El juramento decisorio y el principio de celeridad procesal en los procesos sumarios” - José Andrés, Ulloa Toalombo (2020)
The decision-making oath is a type of testimonial evidence that serves to terminate the process on available rights of the parties. Besides, it should be mentioned that, with the statement made on the truth of the lawsuit, the process ends. This is why the reason for this investigation is focused on the probative value provided by the decision-making oath to resolve a conflict. The main objective is to be a single test that serves to convince the judge. The latter can issue a decision based on the oath taken, resulting in an efficient, fast, and secure administration of justice, thus applying the constitutional principle of procedural speed. Under this background, the research work: "The decision-making oath and the principle of procedural speed in summary proceedings" are intended to describe, and determine whether the decision-making is an effective means of evidence for the termination of the processes on available rights of the parties. Case studies helped to establish whether this mechanism contributes to the speed of the process. The application of investigative instruments helped the research, and a doctrinal, legal, and critical study analyzed this issue to achieve this objective regarding decision-making oath. The results of the investigation agreed that the decision-making oath is useful, pertinent, and conductive evidence. Thus, it might help to end the conflict in summary proceedings quickly, as it is considered evidence and contributes positively with the principle of procedural speed as well as with the principle of procedural economy.